Videodisc Update '77 - R. Kent Wood (Journal of Applied Communications, 1977)
If it were proposed that you were to be told when, on what date, and at what minute you would be allowed to read a research report or a novel, you would be angered and feel that was entirely stifling of your rights and creative efforts.